2011
DOI: 10.1016/j.visres.2010.09.022
|View full text |Cite
|
Sign up to set email alerts
|

A role for DNA methylation in regulation of EphA5 receptor expression in the mouse retina

Abstract: Understanding the mechanisms regulating expression of retinal ganglion cell (RGC) specific and axon-guidance genes during development and in retinal stem cells will be critical for successful optic nerve regeneration. Müller glia have some characteristics of retinal stem cell properties, but in mammals have demonstrated limited potential to differentiate into RGCs. Chromatin remodeling through histone deacetylation and DNA methylation are a potential mechanism for silencing genes necessary for neuronal differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 70 publications
3
31
0
Order By: Relevance
“…3A). Interestingly, the GT box is positioned immediately 3Ј to a cluster of CpG dinucleotides that we previously found to have increased methylation in genomic DNA from the nasal but not temporal retina (25). Therefore, subsequent analysis focused on this site.…”
Section: Regulation Of the Epha5 Promoter Requires Klf16 Binding To Amentioning
confidence: 99%
See 1 more Smart Citation
“…3A). Interestingly, the GT box is positioned immediately 3Ј to a cluster of CpG dinucleotides that we previously found to have increased methylation in genomic DNA from the nasal but not temporal retina (25). Therefore, subsequent analysis focused on this site.…”
Section: Regulation Of the Epha5 Promoter Requires Klf16 Binding To Amentioning
confidence: 99%
“…There is evidence for silencing of EphA5 expression by hypermethylation in cancer (22)(23)(24). We previously showed that total CpG methylation abolishes activity of mEphA5 promoter-reporter constructs in R28 retinal progenitor cells and that transcriptional silencing of the endogenous EphA5 gene in a mouse retinal cell line (ImM10) is reversed by genome-wide demethylation (25). Intriguingly, our prior analysis also showed that in the nasal retina, where EphA5 expression is lowest, CpG methylation is increased specifically in a cluster of CpG dinucleotides immediately downstream of the EphA5 transcription start site.…”
mentioning
confidence: 99%
“…67 New findings have shown that CpG islands in the ephA5 promoter display site-specific differences in methylation that could preferentially activate or repress promoter activity and may contribute to graded ephA5 gene expression in the tectum. 68 More studies, however, have focused on aberrant methylation patterns of Eph receptor and ephrin genes in cancer. Methylation of CpG promoter sequences of ephA1, ephA2, ephA7, ephB2, ephB4 and ephB6 has been reported in several human tumors, including colorectal, prostate and breast cancer.…”
Section: Misregulationmentioning
confidence: 99%
“…How might DNA methylation regulate particular RGC genes? To date, only one study described DNA methylation changes-via bisulfite specific sequencing (a modified PCR method by which methylated CpG regions in primer-specific sequences can be amplified and identified)-in an RGC-expressed gene, EphA5 [80]. EphA5 is a member of the ephrin receptor family of tyrosine kinase receptors, which induce intracellular signaling cascades via binding of ephrin ligands.…”
Section: K27mentioning
confidence: 99%
“…In a Müller cell line, the EphA5 promoter is highly methylated; 5-azacytidineinduced demethylation allowed upregulation of EphA5 mRNA. The authors propose that DNA demethylation may "unlock" the neurogenic potential of Müller cells-considered by some researchers to be multipotent progenitors-and coax these cells to differentiate to RGC-like cells in injury or neurodegeneration [80].…”
Section: K27mentioning
confidence: 99%